2019
DOI: 10.5039/agraria.v14i1a5618
|View full text |Cite
|
Sign up to set email alerts
|

Organic, mineral and organomineral fertilizer in the growth of wheat and chemical changes of the soil

Abstract: The organomineral fertilizers can release organic compounds during their solubilization, and those compounds can affect the plant growth. The aim of this study was to evaluate the initial development of wheat, nutrient accumulation in the plant and soil chemical changes, with the use of organic, mineral and organomineral fertilizers. The experiment was conducted in a greenhouse using an Acrisol cultivated with wheat (Triticum aestivum). Six treatments were tested: 100% of the nutrient recommendation in organom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…This characteristic caused its nutrient more available than OMF for early growth of shallot. The slow release characteristic of OMF had been reported by previous studies (Latifah et al, 2017;Mumbach et al, 2019). ,5(1), 1-7 (2022) The analysis of variance demonstrates that OMF application markedly influenced plant height, leaf number, fresh tuber weight, dry tuber weight, tuber diameter, but no impact on leaf fresh weight, leaf dry weight, and tuber number (Table 1).…”
Section: Resultssupporting
confidence: 71%
“…This characteristic caused its nutrient more available than OMF for early growth of shallot. The slow release characteristic of OMF had been reported by previous studies (Latifah et al, 2017;Mumbach et al, 2019). ,5(1), 1-7 (2022) The analysis of variance demonstrates that OMF application markedly influenced plant height, leaf number, fresh tuber weight, dry tuber weight, tuber diameter, but no impact on leaf fresh weight, leaf dry weight, and tuber number (Table 1).…”
Section: Resultssupporting
confidence: 71%
“…Dashed line represents AEI of 100% present in MF may result in greater efficiency of OM fertilizers (Antille et al, 2014;Borges et al, 2019). In addition, the presence of the organic fraction could reduce the solubility of the fertilizer, resulting in a more gradual release of nutrients into the soil (Grohskopf et al, 2019;Mumbach et al, 2019). However, these benefits were not effective in increase grain yield (Figure 2), thus using OM fertilizers may be economically unfeasible.…”
Section: Efficiency Indicesmentioning
confidence: 99%
“…Evidence suggests that sustained crop yields and soil productivity can better be accomplished with organomineral fertilizers than with mineral inputs (Sá et al, 2017;Grohskopf et al, 2019;Crusciol et al, 2020), although much remains to be learned about the processes involved. Other studies have shown similar crop yields (Corrêa et al, 2016(Corrêa et al, , 2018Frazão et al, 2019;Mumbach et al, 2019). The nature of the organic structure and chemical composition among different organomineral fertilizers is highly variable and results cannot be generalized.…”
Section: Discussionmentioning
confidence: 97%
“…Additional support has recently appeared: according to the Brazilian fertilizer legislation, the mixture of organic residues and mineral fertilizer results in a new category of farm input called organomineral fertilizers (MAPA, 2017). Furthermore, recent studies have demonstrated the positive effects of both conventional and organomineral fertilizers on crop yields (Corrêa et al, 2016;Frazão et al, 2019;Mumbach et al, 2019). However, little is known about the longterm efficacy of organomineral fertilizers on annual crop growth in an acidic Ferralsol, which covers vast areas in Central Brazil.…”
Section: Introductionmentioning
confidence: 99%